2023
DOI: 10.3390/su15054507
|View full text |Cite
|
Sign up to set email alerts
|

Italian Consumers’ Awareness of Climate Change and Willingness to Pay for Climate-Smart Food Products

Abstract: Understanding climate change awareness and its related risks is crucial to plan efficient climate-smart strategies. An online survey was conducted on Italian consumers with the aim to understand consumers’ inclination toward food products obtained with climate-smart strategies. Specifically, consumers’ awareness about climate change and willingness to choose and pay for products derived from climate-smart agriculture were investigated. Results highlighted two targeted consumers, one more interested in economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Simultaneously, the greater impact of environmental information on willingness to pay compared to animal welfare information might stem from our panel of consumers exhibiting a heightened interest in the sustainability aspects of their food choices. Recent literature on Italian consumers indeed indicates an increasing concern for environmental sustainability in food expenditures (Laureti and Benedetti, 2018;Predieri et al, 2023;De Marchi et al, 2024), extending beyond innovative products to conventional ones. This factor likely played a significant role in influencing our findings regarding willingness to pay.…”
Section: Effects Of Information On Premium Price For the Innovative P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, the greater impact of environmental information on willingness to pay compared to animal welfare information might stem from our panel of consumers exhibiting a heightened interest in the sustainability aspects of their food choices. Recent literature on Italian consumers indeed indicates an increasing concern for environmental sustainability in food expenditures (Laureti and Benedetti, 2018;Predieri et al, 2023;De Marchi et al, 2024), extending beyond innovative products to conventional ones. This factor likely played a significant role in influencing our findings regarding willingness to pay.…”
Section: Effects Of Information On Premium Price For the Innovative P...mentioning
confidence: 99%
“…Collectively, there are various studies that illustrate the influence of emotions on individuals' WTP for various products and experiences. If Bates et al (2023) demonstrated that emotions are critical in influencing WTP for meat alternatives, such as insect-based food, other studies indicate that consumers' awareness of climate change can impact their willingness to choose and pay for climate-smart food products (Predieri et al, 2023). In general, people are willing to pay more to experience positive emotions than to avoid negative ones (Lau et al, 2013), hence the analysis of multiple factors simultaneously could be the key to thoroughly understanding which mechanisms, in synergy, most influence WTP.…”
Section: Effects Of Information On Potential Drivers Of Preferences F...mentioning
confidence: 99%